Belanja Modal APBD KABUPATEN-KOTA Di Jawa Tengah Tahun Anggaran 2017 – 2018 - Nurchayati, Nurchayati (Serat Acitya, 2021)
This study aims to determine the effect of Regional Original Income (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), and Revenue Sharing Fund (DBH) on Capital Expenditures in Districts / Cities in Central Java, either simultaneously or partially. The population in this study is the District / City Government Financial Statements in Central Java. This study uses secondary data in the form of Budget Realization Reports (LRA) of 34 districts / cities in Central Java for the 2017-2018 fiscal year. Hypothesis testing in this study using multiple linear regression with t test. The results showed that PAD, DAK and DBH had a positive and significant effect on capital expenditure, while DAU had a negative and insignificant effect on capital expenditure. Simultaneously the variables PAD, DAU, DAK, and DBH affect capital expenditure. Regional governments are expected to pay more attention to the proportion of DAU allocated to the capital expenditure budget.keywords General Allocation Fund, Special Allocation Fund, and Revenue Sharing Fund